2019
DOI: 10.3389/fchem.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 ALD Coating of Amorphous TiO2 Nanotube Layers: Inhibition of the Structural and Morphological Changes Due to Water Annealing

Abstract: The present work presents a strategy to stabilize amorphous anodic self-organized TiO2 nanotube layers against morphological changes and crystallization upon extensive water soaking. The growth of needle-like nanoparticles was observed on the outer and inner walls of amorphous nanotube layers after extensive water soakings, in line with the literature on water annealing. In contrary, when TiO2 nanotube layers uniformly coated by thin TiO2 using atomic layer deposition (ALD) were soaked in water, the growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…These factors have been confirmed by changing the chemical composition, crystallinity, and morphology of the Ti substrate. The SEM image results showed that no pores were formed has been reported by Ng and co-workers [23]. It was inferred that due to the ineffectiveness of the HF solution in the formation of porous titanium oxide is lower than the rate of dissolving the oxide.…”
Section: Figure 2 Ft-ir Analysis Of Tio 2 /Tisupporting
confidence: 60%
“…These factors have been confirmed by changing the chemical composition, crystallinity, and morphology of the Ti substrate. The SEM image results showed that no pores were formed has been reported by Ng and co-workers [23]. It was inferred that due to the ineffectiveness of the HF solution in the formation of porous titanium oxide is lower than the rate of dissolving the oxide.…”
Section: Figure 2 Ft-ir Analysis Of Tio 2 /Tisupporting
confidence: 60%
“…Corresponding samples are later denoted as “+5c TiO 2 ” or “+150c TiO 2 ”, respectively. Based on our previous experience and results, , the nominal thickness of the ALD TiO 2 coating is 0.275 nm and 8.25 nm on flat and sufficiently hydroxylated TiO 2 substrates.…”
Section: Methodsmentioning
confidence: 99%
“…For the majority of biomedical applications, an amorphous state of a material is preferred, and these materials have been frequently used in an aqueous environment. However, soaking of amorphous TNT layers in a water bath transforms them into a polycrystalline anatase structure via the so-called water annealing effect ,, accompanied by significant morphological changes. Recently, we reported a successful approach to prevent the water annealing effect by additional utilization of thin TiO 2 coatings by ALD to protect TNT layers against morphological changes during prolonged water soaking.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies do not show a change of morphology to nanowires but a decoration of the TNT layers with nanoparticles during water annealing as well as during hydrothermal (vapour) treatment. [27][28][29][30] A comparison between water, thermally and hydrothermally annealed TNT layers showed the highest degree of crystallinity and a better performance in photocurrent generation and photocatalysis in case of thermally annealed TNT layers. 27 Plasma and microwave annealing of TNT layers have the advantage of very fast crystallization times of a few minutes, [31][32][33] probably due to a high energy density, high enough to overcome the thermodynamic energy barrier quickly to induce crystallization.…”
Section: Introductionmentioning
confidence: 96%
“…19,20 Higher annealing temperatures lead to mixtures of anatase and rutile structures, and temperatures higher than $800 C lead to a collapse of the nanotubular structure. 21 As the annealing procedure in a muffle oven is time-and energy-consuming (several hours for heating, soaking and cooling of the furnace), numerous other annealing procedures were investigated in the last years, such as rapid thermal annealing, 22 ame annealing, [23][24][25] water, hydrothermal and hydrothermal vapour treatments at low temperatures, [26][27][28][29][30] plasma 31 or microwave 32,33 annealing. Nonetheless, by now none of these annealing procedures could replace the thermal annealing in a muffle oven due to, for instance, a carbon contamination during ame annealing or a very long annealing time in case of water or hydrothermal treatments or simply a less well-developed crystalline phase compared to oven annealing.…”
Section: Introductionmentioning
confidence: 99%